Developing Translation Competence: Pedagogical Insights and Methodological Innovations - Amanova, Gulnoza (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article critically examines contemporary approaches to the development of translation competence, with a particular focus on pedagogical insights and methodological innovations. The central aim of the research is to analyze how translation pedagogy can effectively integrate theoretical principles with practical application in order to enhance students’ professional formation. The study sets out several specific objectives: first, to identify pedagogical strategies that strengthen linguistic, cultural, and technological competences; second, to explore how competence-oriented approaches contribute to systematic translation training; and third, to evaluate the significance of innovative methods in cultivating critical and analytical thinking among students. The research methodology combines comparative analysis of established pedagogical models with case studies drawn from university translation training programs, supported by qualitative evaluation of student performance. This integrated methodological design ensures not only theoretical rigor but also practical applicability, thereby providing a holistic perspective on translation education. The findings reveal that competence-oriented pedagogy, when complemented by task-based learning techniques and technological tools, considerably improves students’ translation accuracy, intercultural sensitivity, and analytical skills. Furthermore, the incorporation of interdisciplinary perspectives, particularly through the use of digital resources, broadens the scope of translation education and equips learners with essential skills for addressing professional challenges in dynamic contexts. The study emphasizes the importance of maintaining a balance between traditional translation methodologies and innovative pedagogical practices. It argues that a student-centered, integrated approach not only raises the quality of translation outcomes but also fosters autonomy, adaptability, and professional readiness. By offering both theoretical insights and pedagogical recommendations, this article contributes to the ongoing scholarly dialogue on translation pedagogy and provides valuable guidance for educators, researchers, and curriculum developers.